2020
DOI: 10.1038/s41598-020-63953-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Autonomic Dysfunction in Murine Ligature-Induced Periodontitis

Abstract: the present study examined the hemodynamics [arterial pressure (Ap), Ap variability (ApV), heart rate (HR), and heart rate variability (HRV)], cardiac function (echocardiographycally), and myocardial inflammation in Balb/c mice submitted to Periodontitis, through the ligation of the left first molar, or Sham surgical procedure. The first protocol indicated that the AP was similar (136 ± 2 vs. 132 ± 3 mmHg in Sham), while the HR was higher in mice with Periodontitis (475 ± 20 vs. 412 ± 18 bpm in Sham), compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
4
9
0
3
Order By: Relevance
“…Moreover, there was no difference between baseline arterial pressure or HR between rats with and without periodontitis. Therefore, these data are in line with previous studies that demonstrated that ligature-induced periodontitis did not affect arterial pressure in mice 67 , and also that the CSN electrical stimulation did not change HR in unanesthetized rats 30 .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, there was no difference between baseline arterial pressure or HR between rats with and without periodontitis. Therefore, these data are in line with previous studies that demonstrated that ligature-induced periodontitis did not affect arterial pressure in mice 67 , and also that the CSN electrical stimulation did not change HR in unanesthetized rats 30 .…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study by Ribeiro et al, on the influence of periodontitis on the cardiovascular system, a 4-0 sterile silk ligature was placed on the first molar of adult male Balb/c mice. The results showed increased levels of inflammatory cytokines in heart tissue, which led to sympathetic activity and cardiac dysfunction [113]. Two studies also reported changes in blood cell composition via the 5-0 ligature model using C57BL/6 mice.…”
Section: Effect On the Cardiovascular And Blood Systemmentioning
confidence: 91%
“…As the influence on sympathetic activity has been reported [113], it is possible that periodontitis affects the whole nervous system due to blood circulation, including the brain. A previous study observed microgliosis and astrogliosis in the hippocampus during a range of 2-12 weeks of 5-0 ligature placement and indicated that the number of glial cells positively correlated with periodontal inflammation [117].…”
Section: Effect On the Central Nervous Systemmentioning
confidence: 99%
“…The jaws were stained with 1% methylene blue (1 g/100 mL, diluted water) for 5 min after the remove soft tissues in 9% hypochlorite for 5 h. Following, the steps and procedures were performed as previously described [22]. Briefly, a digital camera coupled into a D.F.…”
Section: Evaluation Of Alveolar Bonementioning
confidence: 99%
“…Moreover, a growing body of evidence has associated, epidemiologically, periodontal inflammation with cardiovascular diseases, such as arterial hypertension [21]. Our group recently demonstrated that periodontitis impacts the overall arterial pressure variability (APV) and cardiac performance, increases sympathetic activity and myocardial inflammation in Balb/c mice [22]. However, the effects of periodontitis in APV and HRV in hypertensive condition are not yet well established.…”
Section: Introductionmentioning
confidence: 99%